The Wnt pathway: a key network in cell signalling dysregulated by viruses. (8th June 2016) - van Zuylen, Wendy J.; Rawlinson, William D.; Ford, Caroline E.
Summary: Viruses are obligate parasites dependent on host cells for survival. Viral infection of a cell activates a panel of pattern recognition receptors that mediate antiviral host responses to inhibit viral replication and dissemination. Viruses have evolved mechanisms to evade and subvert this antiviral host response, including encoding proteins that hijack, mimic and/or manipulate cellular processes such as the cell cycle, DNA damage repair, cellular metabolism and the host immune response. Currently, there is an increasing interest whether viral modulation of these cellular processes, including the cell cycle, contributes to cancer development. One cellular pathway related to cell cycle signalling is the Wnt pathway. This review focuses on the modulation of this pathway by human viruses, known to cause (or associated with) cancer development. The main mechanisms where viruses interact with the Wnt pathway appear to be through (i) epigenetic modification of Wnt genes; (ii) cellular or viral miRNAs targeting Wnt genes; (iii) altering specific Wnt pathway members, often leading to (iv) nuclear translocation of β‐catenin and activation of Wnt signalling. Given that diverse viruses affect this signalling pathway, modulating Wnt signalling could be a generalised critical process for the initiation or maintenance of viral pathogenesis, with resultant dysregulation contributing to virus‐induced cancers. Further study of this virus–host interaction may identify options for targeted therapy against Wnt signalling molecules as a means to reduce virus‐induced pathogenesis and the downstream consequences of infection. Copyright © 2016 John Wiley & Sons, Ltd.